2013
DOI: 10.3390/ijms14011854
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized Chitosan as an Antimicrobial Agent: Antimicrobial Activity, Mechanism of Action and Biomedical Applications in Orthopedics

Abstract: Chitosan (CS) is a linear polysaccharide with good biodegradability, biocompatibility and antimicrobial activity, which makes it potentially useful for biomedical applications, including an antimicrobial agent either alone or blended with other polymers. However, the poor solubility of CS in most solvents at neutral or high pH substantially limits its use. Quaternary ammonium CS, which was prepared by introducing a quaternary ammonium group on a dissociative hydroxyl group or amino group of the CS, exhibited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(179 citation statements)
references
References 98 publications
1
147
0
8
Order By: Relevance
“…Tan et al (2013) and Chung et al (2011), for example, tested different degrees of deacetylation, molecular weights, densities and quartenized derivatives of chitosan in order to verify its antimicrobial property. In these studies, it was observed that the higher the degree of deacetylation, the greater the antifungal activity of chitosan on Aspergillus flavus, Botrytis cinerea and Colletotrichum lagenarium.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al (2013) and Chung et al (2011), for example, tested different degrees of deacetylation, molecular weights, densities and quartenized derivatives of chitosan in order to verify its antimicrobial property. In these studies, it was observed that the higher the degree of deacetylation, the greater the antifungal activity of chitosan on Aspergillus flavus, Botrytis cinerea and Colletotrichum lagenarium.…”
Section: Resultsmentioning
confidence: 99%
“…2 Chitosan coagulates blood, even in the presence of heparin, and has antibacterial properties, reducing the risk of infection. 5,6 It is used by the British and American armies to achieve rapid and efficient hemostasis in the battlefield, mostly to control bleeding due to bullet wounds. Chitosan exists in three forms: granules, gauze, and nasal plugs.…”
Section: Discussionmentioning
confidence: 99%
“…Quaternary ammonium TMC prepared from amino group moieties, exhibited improved water solubility and stronger bactericidal activity over an entire pH range. So, quaternized sites can increase the potential biomedical applications on anti-infection [19]. Electrospun membranes based on TMC/poly(vinyl pyrrolidone) had high antibacterial activity against S. aureus (749) and E. coli (3588) [15].…”
Section: Most Recent Tmc Applicationsmentioning
confidence: 99%
“…This interaction occurs among cationic N-quaternized moieties ( -+ N(CH 3 ) 3 ) on TMC networks and anionic molecules, such as PDPPG on bacteria cells (Figure 1). It leads to a large increase on membrane permeability, causing structural changes (distortion-disruption), as well as, a severe leakage of cytoplasm constituents and eventually results in the death of bacteria [19]. TMC has greater adsorption capacity onto bacteria cell surface, especially on gram-negative bacteria cell, due its higher negative charge property, regarding the gram-positive bacteria [6].…”
Section: Probably Tmc Bactericidal Mechanismmentioning
confidence: 99%